Teaching English for vocational college students by using a Project-based learning approach - Ismailia, Titik (Journal of English in Academic and Professional Communication, 2024)
Constructing Project-based Learning (PjBL) is crucial for the students of vocational college because it will help them to know more about the real condition in a workplace. It also make them able to do a professional job while studying. This study aims to describe the implementation of Project-based learning (PjBL) in establishing a promotion media in a form of video for 5 minutes duration based on the client need. The client was English Study Program and Language Center State Polytechnic of Jember. The subject of the study was 48 students of English Study Program in the fourth semester. The students had to finish two videos in one semester that was one video as a group project and one video as an individual project. Then, they had to upload those videos in YouTube channel.The method of research was descriptive qualitative. The data taken from the process of developing a video started from planning to product evaluation. This study applied some steps in implementing PjBL that were demanding problem or question, sustained inquiry, authenticity, students’ voice and choice, reflection, critic and revision, and public product. The result showed that the students were able to produce a promotional video in such categories such as travelling to tourism object, event, how to, and advertisement.